1997
DOI: 10.1002/j.2161-007x.1997.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Cult Affiliation and Disaffiliation: Implications for Counseling

Abstract: Between 2 and 5 million young adults are involved in cult groups in the United States. Psychohistorical influences, family dynamics, and religious values affect an individual's susceptibility to joining a cult. Cult affiliation affects the cult member and his or her family members. Although cults have high conversion rates, they also have high rates of disaffiliation. Counselors working with those who join and leave cults need to develop an awareness of clinical symptoms associated with doing so and use approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The strength of the parent-child relationship seems to be critical in its effects on the vulnerability of youth to cult affiliation (Schwartz, 2001). Studies also indicate that families of cult members tend to have a rigid, enmeshed structure (Robinson & Frye, 1997). On the other hand, youths having a secure parental attachment, especially to the father, do not typically affiliate with a cult; a clash of values between parents and child often underlies cult affiliation (Sirkin, 1990)..…”
Section: Relationshipsmentioning
confidence: 99%
“…The strength of the parent-child relationship seems to be critical in its effects on the vulnerability of youth to cult affiliation (Schwartz, 2001). Studies also indicate that families of cult members tend to have a rigid, enmeshed structure (Robinson & Frye, 1997). On the other hand, youths having a secure parental attachment, especially to the father, do not typically affiliate with a cult; a clash of values between parents and child often underlies cult affiliation (Sirkin, 1990)..…”
Section: Relationshipsmentioning
confidence: 99%
“…In a recent writing, Robinson et al (1997) used Sirkin's (1990 five-stage model to characterize the gradual process of cult membership. The five stages are hooking, joining, intensification, social disengagement, and realignment.…”
Section: Cult Membership and Coping With Transitionmentioning
confidence: 99%
“…Concerning the second point: no legitimate religion, political movement-or any group for that matter-has a 100% retention rate, much less a 100% success rate in whatever areas of personal or social functioning that they purport to improve. However, with cults, the member is, more often than not, left in a much worse position than in which he started, whether it t be financially, psychologically, relationally, or some combination of these and other factors (Langone, 1996;Morse & Morse, 1987;Robinson, Frye, & Bradley, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The acknowledgement that cult members are not qualitatively different from the general population in any specific area of adjustment or psychological functioning is an essential component of the current authors' proposed theory. It is worth mentioning, however, that several authors have found that there are some developmental and relational factors that may make some individuals more susceptible to cult recruitment (Buxtant, Saroglou, Casalfiore, & Christians, 2007;Buxtant & Saroglou, 2008;Robinson, Frye, & Bradley, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation